The Relationship Between Childhood Trauma and Insecurity in Adulthood - Rismaida Pariang Ariyanti Napitupulu; Maryana; Wilda Fasim Hasibuan (CV. Era Digital Nusantara, 2026)
This study examines the relationship between childhood trauma and insecurity in adulthood, focusing on the psychological mechanisms that underlie this association. The primary objective is to identify how early adverse experiences contribute to adult insecurity and to analyze the mediating role of attachment styles as well as the moderating effects of resilience and social support. A quantitative cross-sectional design was employed, involving 247 participants aged 18–35 years. Data were collected using standardized instruments, including the Childhood Trauma Questionnaire (CTQ), Experiences in Close Relationships Scale (ECR-R), and validated measures of resilience and perceived social support. Statistical analyses were conducted using correlation, regression, mediation, and moderation techniques. The results indicate that childhood trauma significantly predicts adult insecurity, with attachment insecurity serving as a key mediating factor. Individuals with higher trauma exposure tend to develop maladaptive attachment patterns, which in turn increase vulnerability to insecurity in adulthood. Furthermore, resilience and social support were found to significantly reduce the strength of this relationship, highlighting their protective role. These findings emphasize that the long-term impact of childhood trauma is not only direct but also operates through complex psychological pathways. The study underscores the importance of early intervention, attachment-based approaches, and strengthening protective factors to reduce insecurity in adulthood.